2002
DOI: 10.4049/jimmunol.168.7.3165
|View full text |Cite
|
Sign up to set email alerts
|

Germinal Center B Cells Constitute a Predominant Physiological Source of IL-4: Implication for Th2 Development In Vivo

Abstract: Protective immunity depends upon the capability of the immune system to properly adapt the response to the nature of an infectious agent. CD4+ Th cells are implicated in this orchestration by secreting a polarized pattern of cytokines. Although Th2 development in animal models and in human cells in vitro to a large extent depends on IL-4, the nature of the cells that provide the initial IL-4 in vivo is still elusive. In this report, we describe the anatomical localization as well as the identity of IL-4-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…Accordingly, follicular CD4 ϩ T cells, initially primed on T cell zone-localized dendritic cells (DCs), are likely to receive a second boost of differentiation signals during the interaction with GC B cells. We have recently shown that GC B cells produce IL-4 in vivo, suggesting that GCs do provide an appropriate microenvironment for Th2 development (25). In this study we demonstrate that although CD4 ϩ T cells from human tonsil lack immediate effector functions, they develop into cytokine-secreting cells after polyclonal activation in vitro.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Accordingly, follicular CD4 ϩ T cells, initially primed on T cell zone-localized dendritic cells (DCs), are likely to receive a second boost of differentiation signals during the interaction with GC B cells. We have recently shown that GC B cells produce IL-4 in vivo, suggesting that GCs do provide an appropriate microenvironment for Th2 development (25). In this study we demonstrate that although CD4 ϩ T cells from human tonsil lack immediate effector functions, they develop into cytokine-secreting cells after polyclonal activation in vitro.…”
supporting
confidence: 53%
“…We have recently shown that IL-4 production in human mucosaassociated lymphoid tissues is highly confined to GCs where B cells constitute a predominant cellular source (25). In response to platelet activating factor, GC B cells also secrete relatively large amounts of IL-4 in vitro (37).…”
Section: Identification Of a Follicular Th Cell Subset Expressing Crtmentioning
confidence: 99%
“…One scenario is that during B cell repopulation, stochastic events and environmental hits fail to converge and reproduce the breakdown of tolerance characteristic of the initial disease. Alternatively, the absence of B cells could create profound changes in other immune cells, including T cell subsets (altered T helper cell polarization, defective migration of CXCR5ϩ follicular T helper cells, or T regulatory cell expansion) (7,8,(38)(39)(40) and DCs (9), as has been suggested in recent studies (41,42). Finally, a reconstitution dominated by immature and virgin B cells may lead preferentially to T cell anergy (10).…”
Section: Discussionmentioning
confidence: 94%
“…Secreted Ags can undergo Ag processing and presentation following receptor-mediated uptake into B cells, either through Ag-specific Ig (28,29) or other receptors such as the transferrin receptor (30). B cells, especially germinal center B cells, are strong producers of IL-4, the lymphokine that determines the raising of type 2 CD4 ϩ T cell responses (31,32). Also, it is known that when B cells are ablated, the generation of IFN-␥-producing CD4 ϩ T cells is increased (33).…”
Section: Discussionmentioning
confidence: 99%